2005
DOI: 10.1007/s11745-005-1465-2
|View full text |Cite
|
Sign up to set email alerts
|

A molecular dynamics study of an archaeal tetraether lipid membrane: Comparison with a dipalmitoylphosphatidylcholine lipid bilayer

Abstract: Molecular dynamics simulations of an archaeal membrane made up of bipolar tetraether lipids and a dipalmitoylphosphatidylcholine (DPPC) lipid membrane were performed and compared for the first time. The simulated archaeal membrane consists of a pure monolayer of asymmetrical lipids, analogous to the main polar lipid [MPL; Swain, M., Brisson, J.-R., Sprott, G.D., Cooper, F.P., and Patel, G.B., (1997) Identification of beta-L-Gulose as the Sugar Moiety of the Main Polar Lipid of Thermoplasma acidophilum, Biochim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
(52 reference statements)
1
20
0
Order By: Relevance
“…Based on our results presented here, it is likely that with respect to their permeability, fluidity and thermal stability, binary lipid mixtures of diether C 25,25 lipids and DPPC behave similarly as tetraether lipid and DPPC mixtures, although they are structurally different [9,10]. The model tetraether lipid membrane can be defined as an assembly of tightly packed molecules [27].…”
Section: Accepted M Manuscriptmentioning
confidence: 71%
“…Based on our results presented here, it is likely that with respect to their permeability, fluidity and thermal stability, binary lipid mixtures of diether C 25,25 lipids and DPPC behave similarly as tetraether lipid and DPPC mixtures, although they are structurally different [9,10]. The model tetraether lipid membrane can be defined as an assembly of tightly packed molecules [27].…”
Section: Accepted M Manuscriptmentioning
confidence: 71%
“…Molecular dynamic (MD) simulations on membranes composed of an analog of the main polar lipids (MPL) from T. acidophilum seem to contradict the 31 P NMR results (Nicolas, 2005) because the simulation showed that, at temperatures a few degrees above the growth temperature, the MPL analog does not exhibit a significant lateral diffusion, at least not at the time scale of the simulation (Nicolas, 2005). However, the MD simulations did show higher molecular order for MPL-like lipids than for conventional diester lipids (Nicolas, 2005).…”
Section: Btl Liposomes Derived From S Solfataricus and From T Acidomentioning
confidence: 96%
“…Several other models of tetraether membranes were developed. [16][17][18][19][20][21] We studied di-and tetra-ether membranes by MD simulations, where the negative charge on tetraether membranes from S. acidocaldarius was neutralized by counterions. 22 Analysis of the simulations revealed that the size of the counterions affected the physical properties of the membranes.…”
Section: Introductionmentioning
confidence: 99%